Impact of pandemic service changes on ethnic inequalities in maternal and perinatal outcomes in England: a population-based study - Ibrahim, Buthaina; Jardine, Jennifer Elizabeth; Lenguerrand, Erik; Judge, Andrew; Khalil, Asma; Draycott, Tim; Iliodromiti, Stamatina (BMJ open, 2025)
ObjectiveIn the UK and worldwide, there are substantial ethnic inequalities in maternal and perinatal care and outcomes. We aim to assess the impact of the unprecedented change in care provision during the COVID-19 pandemic on inequalities in adverse maternity outcomes.DesignRetrospective cohort study using structured electronic health record data.SettingEnglish hospital trusts providing maternity care.ParticipantsWomen giving birth and babies born in the National Health Service (NHS) in England between 1 April 2018 and 31 March 2021, in three time groups: prepandemic, the first pandemic wave (26 March 2020 to 30 June 2020) and second pandemic wave (1 July 2020 to 31 March 2021). Self-reported ethnicity was grouped into White, South-Asian, Black, Mixed and Other.Main outcome measuresComposite and component measures of maternal (emergency caesarean section, obstetric anal sphincter injury, hysterectomy, sepsis, anaesthetic complications and prolonged hospital stay) and perinatal (stillbirth, neonatal death, preterm birth, brain injury, small for gestational age and prolonged hospital stay). Poisson regression was used to compare relative risks between different ethnic groups.Findings1.54 million maternal and 1.43 million neonatal records were included. The overall incidence of adverse outcomes per 1000 births initially decreased maternal: from 308.0 (95% CI 307.0 to 309.0) to 291.0 (95% CI 311.4 to 314.9) (p<0.001); perinatal: from 133.0 (95% CI 132.3 to 133.7) to 111.9 (95% CI 110.1 to 113.7) (p<0.001)), but then increased in the second pandemic period (maternal: 313.2 (95% CI 311.4 to 314.9) (p<0.001); perinatal 118.9 (95% CI 117.7 to 120.0) (p<0.001)). The risk of adverse outcomes was higher in women and babies from all ethnic minority groups compared with White women in both pandemic periods. Black and South-Asian women and babies were approximately 25% more likely to sustain adverse outcomes. While similar overall changes in adverse outcomes were seen in all groups, existing inequalities were sustained throughout the pandemic periods.InterpretationExisting inequalities in adverse maternal and perinatal/neonatal outcomes were maintained, not tempered, during the pandemic, despite substantial changes to maternity services and care. Further research on possible interventions to reduce inequality is needed.